Current situation and solutions for implementing policies on patent exploitation support to foster innovation in supporting industry enterprises in Vietnam - Do Duc Nam (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
This article focuses on analyzing the current situation regarding the implementation of support policies for patent exploitation to serve innovation in supporting industry enterprises. Based on the analysis of advantages and existing limitations in both policies and practical application for supporting industry enterprises, the article proposes recommendations and solutions to promote and enhance the effectiveness of implementing support policies on patent exploitation to meet the innovation needs of supporting industry enterprises in Vietnam today. Code: 24122401